Influence of Mulching and Planting Geometry on Seed Quality and Ripe Fruit Rot Incidence of Bell Pepper (Capsicum annuum L.). - Verma, Rohit; Mehta, D. K.; Thakur, K. S.; Kumar, Nitish (International Journal of Bio-resource and Stress Management, 2019)
A experimental trial was conducted at Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Solan, HP, India during kharif season 2013, to evaluate the influence of mulching and planting geometry on seed quality and ripe fruit rot incidence of bell pepper (capsicum annuum L.) using cv. Solan Bharpur. Planting geometry comprised of three row layouts and two plant layouts. The different treatments involved in the present studies were, four mulches (No mulch, Black-plastic mulch, Silver-black plastic mulch and Crop residue mulch), three row layouts (Single row 60×45 cm2, Double row (75+45)×45 cm2), and Double row (90+30)×45 cm2) and two plant layouts (Rectangle/square, and Triangle) with constant plant population i.e. 37037 plants ha-1. Thus there were 24 (4×3×2) treatment combinations. The field experiment was laid in Split-Split Plot Design replicated three times while laboratory experiment was conducted in Completely Randomized Block Design (Factorial) with four replications. The results revealed that significantly higher germination percentage (95.66%), seedling length (9.98 cm), seedling dry weight (2.99 mg), seed vigour index-Length and Mass (954.74 and 286.05 respectively) was recorded in treatment combination of silver-black plastic mulch+double row (75+45)×45 cm2+triangle plant layout. However the interaction effect of mulching and planting geometry on 1000 seed weight and ripe fruit rot incidence % was found to be non significant.